Simple resistance-to-period converter for resistive sensors - Tongpakpanang, Jaturon; Rerkratn, Apinai; Kaewpoonsuk, Anucha; Riewruja, Vanchai; Petchmaneelumka, Wandee (My University, 2012)
A method for realization of resistance-to-period converter is introduced in this article. The principle of converter utilizes the behavior of designed astable multivibrator, which is implemented using commercial available and low cost devices. The operation of proposed converter circuit is in current mode. Therefore, the resistance is linearly converted to period and also converted to frequency with invert proportional relationship. The conversion gain of the proposed converter can be adjusted by electronic means. The configuration of the proposed converter is simple and small in size. Experimental results verifying the proposed converter performance are included in detail. The relative error of about 0.8 % is observed. © 2012 ICROS.
Keywords: Interface circuit; Resistance-to-period converter; Resistive sensor